DETERMINANT FACTORS OF ATTACK EFFICACY IN HIGH-LEVEL MEN’S VOLLEYBALL: WHAT DOES DISTINGUISH THE MIDDLE-ATTACKER PERFORMANCE? (Kinesiology, 2024)
This study aimed to identify determinant factors of attack efficacy considering the effects of reception, attack tempo, attack performance, setting type and attack type. Firstly, 19,454 offensive actions of complex I of the Brazilian Volleyball Men’s Super League were considered and analyzed separately from the middle, wing, and opposite attacker standpoints. The middle attack was the most effective, so the 5,259 offensive actions were analyzed considering the setting type and the attack direction. The independent variables were the quality of reception, type and direction of attack, whereas attack performance was the dependent variable. We found that the middle attack efficacy was related to excellent receptions, right tempo and left tempo (near the setter), and power attack. The results can afford coaches with the key information for better training plan designs and preparation for competition.Key words: factors in sport performance, tactics, performance, attack efficacy